Workload and Burnout on Healthcare Worker Performance in Remote Riau Islands Puskesmas, Indonesia: Moderating Role of Organizational Support - Dahlan Gunawan; Elly Rumengan; Malahayati Rusli Bintang; Etty Sri Wahyuni (Fundamental and Applied Management Journal, 2026)
Healthcare workers (HCWs) in remote archipelagic regions bear a disproportionate workload that threatens both their psychological wellbeing and the quality of primary care. This study examines the effect of workload on burnout and HCW performance at community health centres (Puskesmas) in remote island districts of Riau Islands Province, Indonesia, positioning organizational support as a moderating variable. Grounded in the Job Demands–Resources (JD-R) model, Conservation of Resources (COR) theory, and Organizational Support Theory (OST), a quantitative cross-sectional survey was administered to 186 HCWs across 18 Puskesmas in Natuna, Lingga, and Kepulauan Anambas, selected through proportionate stratified random sampling. Workload was measured with the NASA-Task Load Index, burnout with the Maslach Burnout Inventory (MBI-HSS), performance with a validated 20-item instrument, and organizational support with the Survey of Perceived Organizational Support. Moderated-mediation analysis (PROCESS Model 59, 5,000 bootstrap samples) showed that workload significantly increased burnout (β = 0.512, p < 0.001) and reduced performance (β = −0.374, p < 0.001), with burnout partially mediating the relationship (indirect effect = −0.189, 95% CI [−0.261, −0.121]). Organizational support significantly buffered both the workload–burnout path (β = −0.284, p = 0.003) and the workload–performance path (β = 0.231, p = 0.011). The study's novelty lies in demonstrating an actionable buffering mechanism in DTPK settings and proposing an integrated organizational-support intervention model as a policy solution. Because organizational support can be strengthened quickly and at low cost through supervisory responsiveness, workload rationalisation, recognition, and wellbeing support it provides district health offices in DTPK settings with a fast and affordable intervention lever to protect HCW performance where structural workforce solutions remain slow and costly.